2016
DOI: 10.1080/01658107.2016.1179767
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Features of Idiopathic Intracranial Hypertension Persist After Resolution of Papilloedema

Abstract: Papilloedema is a key clinical finding in the diagnosis of idiopathic intracranial hypertension (IIH). However, newly proposed criteria allow diagnosis without papilloedema only if certain neuroimaging features are present. It is currently unclear if these findings persist upon resolution of papilloedema and IIH. A retrospective chart review identified three groups of patients (six per group) who had received orbital imaging within 4 weeks of fundoscopic examination: (1) IIH patients without active papilloedem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Noteworthy, the patients were being treated with acetazolamide, that has been shown to induce complete recovery of papilledema and improvement in the height of the midsagittal pituitary height, possibly affecting the observed results ( 11 , 24 ). On the other hand, the re-expansion of the pituitary gland does not occur as rapidly as the resolution of papilledema, and in fact some authors propose to integrate the follow-up not only with the fundus oculi evaluation, but also with MRI, as the persistence of an ES and posterior globe flattening may be useful for IIH detection even after the resolution of papilledema and the normalization of ICP ( 25 ). It should also be emphasized that acetazolamide has not always proved effective in restoring the pituitary morphology, which was then achieved through a lumboperitoneal shunt ( 11 ) or serial lumbar punctures ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the patients were being treated with acetazolamide, that has been shown to induce complete recovery of papilledema and improvement in the height of the midsagittal pituitary height, possibly affecting the observed results ( 11 , 24 ). On the other hand, the re-expansion of the pituitary gland does not occur as rapidly as the resolution of papilledema, and in fact some authors propose to integrate the follow-up not only with the fundus oculi evaluation, but also with MRI, as the persistence of an ES and posterior globe flattening may be useful for IIH detection even after the resolution of papilledema and the normalization of ICP ( 25 ). It should also be emphasized that acetazolamide has not always proved effective in restoring the pituitary morphology, which was then achieved through a lumboperitoneal shunt ( 11 ) or serial lumbar punctures ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the optic nerve configuration does not return to baseline values after CSF pressure-lowering therapy. [16] Because all of the patients in our study with IIH had grades 1–3 papilledema at the time of imaging – indicating that the CSF pressure was still high – our LC measurements may reflect the chronic structural changes seen in IIH cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is not entirely clear how a long-term increase of ICP causes the size reduction of the pituitary gland, but it is thought to be the result of a herniation of arachnocele through the diaphragma sellae (25). Interestingly, most abnormal morphometric neuroimaging findings do not improve after CSF pressure has been normalized and papilledema has resolved (26). However, healthy participants in research studies or patients who are scanned for a different reason may show an "empty sella."…”
Section: Structural Mrimentioning
confidence: 99%